PWE-006 Enhancing the diagnostic yield of brush cytology for malignant biliary strictures: early experience with the infinity™ cytology brush. (22nd June 2015) - Bakir, I Al; Wolfson, P; Sayers, R; Maddox, A; Shariff, M; King, A; Leahy, A
Abstract : Introduction: The diagnostic yield of endobiliary brush cytology remains inadequate, with published rates ranging from 30–57%. 1 The Infinity TM cytology brush (US Endoscopy, Ohio, USA) aims to improve detection rates by using a combination of stiffer outer bristles to create a tissue defect, and softer inner bristles to capture abraded material. 2 Furthermore, gaps between the bristle segments help capture more tissue in each brush and the brush also has a dedicated catheter that can be flushed/aspirated to retrieve additional cells. We aim to determine whether introducing this new brush could result in an improved diagnostic yield. Method: In November 2013, our endoscopy department switched from using a standard cytology brush (Combo Cath TM Rx Cytology Brush, Boston Scientific, Massachusetts, USA) to the Infinity TM cytology brush. Our electronic endoscopy system was retrospectively analysed between April 2010 and December 2014. All patients with pancreatic cancer or cholangiocarcinoma who had brush cytology taken at endoscopic retrograde cholangio-pancreatography were included. A diagnosis of cancer was made by the upper gastrointestinal cancer multidisciplinary team using radiological, histological and/or cytological findings. Patients subsequently found to have benign disease were excluded from the analysis. All strictures were brushed with a minimum of 10 passes, with the addition of bile aspiration when the Infinity TM cytology brush was used. A positive cytological sample was defined as containing either malignant or dysplastic cells. A negative cytology result only contained benign and/or inflammatory cells. All samples were independently reviewed by a consultant histopathologist blinded to the procedure. Group differences were analysed by the Fisher–s exact test. Results: Conclusion: Our initial experience shows that the use of the Infinity™ cytology brush does not increase diagnostic yield. Further trials of this cytology brush at other centres are required to determine whether our findings are reproducible. Disclosure of interest: None Declared. References: Larghi A, Waxman I. Differentiating benign from malignant idiopathic biliary strictures: are we there yet? Gastrointest Endosc. 2007 Jul;66(1):97-9 Infinity ERCP sampling device international specification sheet. Available on 27 February 2015 at http://www.usendoscopy.com/∼/media/Files/Documents/Spec-Sheet-International/cytology_INTL_spec_sheet_760893B.pdf